Update of data from the world apheresis association (WAA) registry - Stegmayr, Bernd; Vrielink, Hans; Witt, Volker; Derfler, Kurt; Deeren, Dries; Bojanic, Ines; Gasova, Zdenka; Kielstein, Jan T; Tehuteru, Edi Setiawan; Kiraka, Grace; Audzijoniene, Judita; Griskevicius, Antanas; et al. (Transfusion and apheresis science, 2025)
The WAA registry has been active since 2002. It allows bed side registration of safety and efficacy data. The data each center enters is accessible for its own use but also used for merged analysis. Most types of procedures are represented. Treatments of many severe diseases as well as the collection of autologous and donor cells for therapeutic use especially in oncologic diseases are recorded. Previous reports have shown a successive reduction in adverse events (AE) over the years. The aim of the present report is to update data of the risk for AE during the years from 2013 to Oct 2024. Contributions of 44 centers from 20 countries were analysed. Over these years, more than 169,000 apheresis procedures have been registered in more than 26,000 patients. During the study period the mean incidence of AE, merged for all types of procedures, was 1.6 /100 procedures for mild, 2.0/100 for moderate and 0.20/100 for severe AE, and reduced since 2013. Since 2002, death due to apheresis could not be excluded in one patient. There was an increased risk of hypotension during apheresis in patients with neurological diagnoses (ICD-10 chapter G) versus those with diseases of the musculoskeletal or connective tissue (ICD-10 chapter M) and vice versa for urticaria and tingling. In conclusion, the present data show the risk for various degrees of AE in apheresis procedures. Many patients suffer from severe illness and apheresis is often offered as a rescue therapy. Although the risk of death due to the apheresis procedure is extremely rare the concomitant severe disease itself poses a risk for severe events.
Keywords: Risks; Blood Component Removal; Registries; Apheresis; registrace; lidé; Female; mužské pohlaví; Male; separace krevních složek; Adverse events; Fluid replacement; ženské pohlaví; Humans